Emerging from the flow of time: lectotypification of the name Zannichellia peltata Bertol. (Potamogetonaceae) and its taxonomic history - Lastrucci, Lorenzo; Ardenghi, Nicola M. G.; Alessandrini, Alessandro (Phytotaxa, 2019)
Zannichellia peltata Bertoloni (1854: 10) was described in the 10th volume of Flora Italica. This is one of the two species of Zannichellia Linnaeus (1753: 969) that he recorded from Italy (the other being Z. palustris Linnaeus [1753: 969]). Antonio Bertoloni (1775−1868) described the species based on a Gasparrini collection from the vicinity of Rosarno (Reggio Calabria) in southern Italy: “Habui ex fossis, et aquis quietis Calabriae prope Rosarno a Gasparrinio”.